Gig Economy dan Doom Spending: Apakah Profesi Affiliator Cerminan Kebebasan Generasi Z? - Putu Ayu Titha Paramita Pika; Ni Kadek Kirana Iswari Dewi; I Nengah Wirsa; Ni Putu Nina Eka Lestari (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The rapid growth of digital platforms has encouraged many Generation Z workers to pursue flexible income sources, including becoming TikTok affiliators. Although this profession is often perceived as a symbol of freedom in the Gig Economy, previous studies have not examined how affiliator work may also shape consumption pressure and trigger emotional spending patterns such as Doom Spending. This study aims to explore the experiences of Gen Z affiliators in navigating platform-based work, building consumer trust, and managing the psychological and economic uncertainties embedded in algorithm-driven systems. Using a qualitative approach, data were collected through in-depth interviews and documentation involving five affiliators, four consumers, and one business owner whose products were promoted through TikTok Affiliate. The data were analyzed using thematic analysis supported by NVivo 15. The findings show that affiliators are motivated by flexible work arrangements, income expectations, and opportunities for creative expression. Soft-selling techniques and trend-based visual content are used to build engagement and trust, while authenticity remains central to gaining consumer confidence. However, the study also reveals a strong dependence on algorithmic visibility, income instability, and emotional pressure to stay relevant in fast-moving digital trends. These conditions contribute to the emergence of FOMO and impulsive consumption, reinforcing Doom Spending among Gen Z. The study highlights how affiliator work functions not only as an economic activity but also as a cultural practice that shapes identity, consumption patterns, and financial vulnerability in the Gig Economy.